The efficacy and safety of apixaban: what has changed in 12 years of its use in real clinical practice? - E. Р. Panchenko («REMEDIUM GROUP» Ltd., 2023)
This review examines the position of apixaban among other direct oral anticoagulants in patients with atrial fibrillation (AF) and venous thrombosis in randomized clinical trials and real clinical practice. Since the advent of apixaban, many studies of real clinical practice (RCP) and meta-analyses have appeared. RCP studies have fully confirmed the efficacy and safety of apixaban. Now we have data that au pixaban is equally effective and safe in elderly and senile people and younger patients, as well as in patients with reduced creatinine clearance. The efficacy and safety of apixaban has been confirmed in patients with AF with the presence of diseases of several vascular basins, in patients with AF and angina, including acute coronary syndrome, treated by coronary artery stenting and conservatively. An important property of apixaban is safety, which can be traced in almost all studies, which made it possible to successfully apply it in people with a high risk of bleeding, namely in patients with active cancer and venous thrombosis. Thus, RCP studies in patients with AF, including the elderly and senile patients with chronic kidney disease, many concomitant diseases, as well as patients with VTEC, confirmed the results of randomized clinical trials of apixaban. The drug appears to be an effective and at the same time the safest anticoagulant. The safety image of Apixaban which has become noticeable in all RCTs (in patients with atrial fibrillation, VTEC, including patients with active cancer) was confirmed both in real clinical practice studies and meta-analyses, and allowed it to be successfully used in the category of patients which are at highest risk for bleeding.